The use of confocal Raman spectroscopy to characterise the microstructure of complex biomaterials: foods. Issue 3 (2002) - Pudney Pudney, Paul D. A. Paul D. A.; Hancewicz Hancewicz, Thomas M. Thomas M.; Cunningham Cunningham, Dale G. Dale G.
Abstract : The properties and behaviour of many biomaterials often depends crucially on their microstructure. This is especially true of the largest class of biomaterials in use, foods. They include general properties, e.g., food texture, and others, such as spreadability of margarine/butter, pourablity of ketchup, scoopablity of ice cream, and also flavour release (a problem that has much in common with drug delivery), to name but a few. Thus, most food laboratories do a large amount of work in rheology and microscopy to relate structure and properties. However, a knowledge gap exists, i.e., what is the location and quantity of ingredients/molecules within a structure? Both of these questions need to be answered if a complete understanding is to be obtained. The "what is where" question can sometimes be answered by using various microscopic labelling techniques, although there can be many problems with these methods. Bulk separation is often attempted, followed by some kind of more classical analysis, but this is often either not possible or may cause some kind of uncontrolled perturbation. Thus, the ability to obtain quantitative information in situ within a microstructure has been an unobtained goal in much of food science research. These types of questions are, of course, also asked in many related fields of research. This paper will illustrate how the advances in confocal Raman spectroscopy have allowed this problem to be tackled, in a non‒invasive way. It will show how careful development of experimental procedures and advances in data analysis methods, allow even quantitative maps of microstructures to be obtained. The details of this approach will be described including a discussion of the limitations of current methods, especially depth resolution, and how these were overcome. The use of these methods will be illustrated with a gelled mixture of two carbohydrate polymers, κ‒carageenan and gellan. Despite being similar polymers, and hence having highly overlapping spectra, the pure spectral components can be separated using a chemometrics based method, multivariate curve resolution (MCR). The principles of this method will be described. Under certain concentration regimes these two biopolymers phase separate. This property can be used to produce different microstructures. Two different microstructures were produced and mapped using Raman spectroscopy. This data was analysed using the MCR method to show the relative locations of the two polymers within the microstructure. Furthermore, by augmenting the data from these maps with calibration data for the two bioploymers, quantitative maps were produced. The resultant concentrations can then be used to produce tie lines for the κ‒carageenan/gellan phase diagram, which is essential for understanding and manipulating the structure and properties in a systematic way. This methodology can be readily extended to much more complex multicomponent systems, such as complete food products. This paper shows that the combination of the confocal Raman spectroscopy and MCR data analysis methodology is very powerful and is readily applicable in many areas of research, especially the biomaterial/biomedical fields.